Kesehatan Ikan, Identifikasi, dan Analisis Prevalensi Parasit Ikan di Danau Buyan, Buleleng Bali - Reboin Sitompul; Sang Ayu Made Putri Suryani; I Wayan Arya (Fakultas Pertanian, Universitas Warmadewa, 2019)
This study aims to determine the condition factor (FK) of fish that live wildly on Lake Buyan and record the types of fish parasites that exist, by identifying parasites in fish samples caught by fishers both fishing with fishing rods and with nets. Then counting prevalence of types of parasites found.This study uses the descriptive exploitative research method, namely by conducting a series of observational activities on the object under study in this case are the fish that are on Lake Buyan both fish that have economic value and wild fish that have no economic value. Data retrieval techniques in this study were carried out by direct observation or observation of objects studied in the field, and microscope observations in the laboratory on sample fish. The condition factor (FK) is different for each type of fish and there is a decrease in FK in each fish, namely the observation period in August 2018. Nilem fish has FK which is 1.66 (less healthy) compared to other fish.In this study nine species of parasites were identified in seven species of fish, while the parasites were: Dactyrogilus sp, Gyrodactilus sp, Tricodina sp, Vorticellasp, Oodinium sp, Saprolegniasp, Argulus sp, Lernaeasp, Icthyoptiriussp. All of which belong to the ectoparasites which attack the outside of the body of the fish such as skin, scales, fins, gills and head.The prevalence of each type of parasite varies for each type and each observation period. The highest prevalence in June was Tricodina sp with a value of 5.71%. In July the highest was Saprolegnia sp 8.57%, in August the highest was Saprolegnia sp and Lernaea sp which amounted to 10%.